Dickkopf-3 attenuates pressure overload-induced cardiac remodelling. (9th January 2014) - Zhang, Yan; Liu, Yu; Zhu, Xue-Hai; Zhang, Xiao-Dong; Jiang, Ding-Sheng; Bian, Zhou-Yan; Zhang, Xiao-Fei; Chen, Ke; Wei, Xiang; Gao, Lu; Zhu, Li-Hua; Yang, Qinglin; et al.
Abstract: Aims: Dickkopf-3 (DKK3), a secreted protein in the Dickkopf family, is expressed in various tissues, including the heart, and has been shown to play an important role in tissue development. However, the biological function of DKK3 in the heart remains largely unexplored. This study aimed to examine the role of DKK3 in pathological cardiac hypertrophy. Methods and results: We performed gain-of-function and loss-of-function studies using DKK3 cardiac-specific transgenic (TG) mice and DKK3 knockout (KO) mice (C57BL/6J background). Cardiac hypertrophy was induced by aortic banding. Cardiac hypertrophy was evaluated by echocardiographic, haemodynamic, pathological, and molecular analyses. Our results demonstrated that the loss of DKK3 exaggerated pressure overload-induced cardiac hypertrophy, fibrosis, and dysfunction, whereas the overexpression of DKK3 protected the heart against pressure overload-induced cardiac remodelling. These beneficial effects were associated with the inhibition of the ASK1-JNK/p38 (apoptosis signal-regulating kinase 1-c-Jun N-terminal kinase/p38) signalling cascade. Parallel in vitro experiments confirmed these in vivo observations. Co-immunoprecipitation experiments suggested that physical interactions occurred between DKK3 and ASK1. Moreover, rescue experiments indicated that, in DKK3 TG mice, the activation of ASK1 using a cardiac-specific conditional ASK1 transgene reduced the functionality of DKK3 in response to pressure overload; furthermore, the inactivation of ASK1 by dominant-negative ASK1 rescued pressure overload-induced cardiac abnormalities in DKK3 KO mice. Conclusion: Taken together, our findings indicate that DKK3 acts as a cardioprotective regulator of pathological cardiac hypertrophy and that this function largely occurs via the regulation of ASK1-JNK/p38 signalling.